RESIDUAL STRESS DISTRIBUTION FOR A SINGLE PASS WELD IN PIPE (Journal of Engineering, 2010)
Heat input due to the welding of mild steel pipe causes a temperature gradient in the parent metal. After welding and temperature cooling down, residual stresses appear around welding zone which reduces the weld strength. Residual stresses are a result of the temperature gradient and the dependency of material properties on the temperature, such as yield strength, elasticity modulus, and thermal expansion coefficient.In this study, a typical flat joint of a single pass weld in a thin pipe was studied analytically and numerically. Analytical approach is performed by exploring a simple method to calculate the magnitude of residual stress in terms of the weld shrinkage behavior. Numerical analysis is performed by applying non-linear transient heat transfer analysis using welding parameters, such as heat generation, free or force convection with ambient, are performed using a general purpose FE package ANSYS 8.0 in order to obtain the temperature distribution in the welded parts. A non-linear thermal-elastic-plastic stress analysis is then performed using the same package to predict the stress fields during and after welding.